Structural analysis and molecular docking of trypanocidal aryloxy-quinones in trypanothione and glutathione reductases: a comparison with biochemical data. Issue 8 (11th June 2017) - Vera, Brenda; Vázquez, Karina; Mascayano, Carolina; Tapia, Ricardo A.; Espinosa, Victoria; Soto-Delgado, Jorge; Salas, Cristian O.; Paulino, Margot
Abstract : A set of aryloxy-quinones, previously synthesized and evaluated against Trypanosoma cruzi epimastigotes cultures, were found more potent and selective than nifurtimox. One of the possible mechanisms of the trypanocidal activity of these quinones could be inhibition of trypanothione reductase (TR). Considering that glutathione reductase (GR) is the equivalent of TR in humans, biochemical, kinetic, and molecular docking studies in TR and GR were envisaged and compared with the trypanocidal and cytotoxic data of a set of aryloxy-quinones. Biochemical assays indicated that three naphthoquinones (Nq-h, Nq-g, andNq-d ) selectively inhibit TR and the TR kinetic analyses indicated thatNq-h inhibit TR in a noncompetitive mechanism. Molecular dockings were performed in TR and GR in the following three putative binding sites: the catalytic site, the dimer interface, and the nicotinamide adenine dinucleotide phosphate-binding site. In TR and GR, the aryloxy-quinones were found to exhibit high affinity for a site near it cognate-binding site in a place in which the noncompetitive kinetics could be justified. Taking as examples the three compounds with TR specificity (TRS) (Nq-h, Nq-g, andNq-d ), the presence of a network of contacts with the quinonic ring sustained by the triad of Lys62, Met400′, Ser464′ residues, seems to contribute hardly to the TRS. CompoundNq-b, a naphthoquinone with nitrophenoxy substituent, proved to be the best scaffold for the design of trypanocidal compounds with low toxicity. However, the compound displayed only a poor and non-selective effect toward TR indicating that TR inhibition is not the main reason for the antiparasitic activity of the aryloxy-quinones.